Николай Иванович Вавилов: из эпистоляр. наследия, 1929-1940 гг. / Н. И. Вавилов - Вавилов Николай Иванович (Научное наследство, 1987)
Экземпляры: КХ (20130219) / Инвентарный номер: 905665 / Цена: 5.40 / Сис.шифр: 57(09) / Авт.знак: В 12 / ГРНТИ: 68 / ББК: 28